Impaired Coupling between the Dorsomedial Prefrontal Cortex and the Amygdala in Schizophrenia Smokers Viewing Anti-smoking Images - Potvin, Stéphane; Tikàsz, Andràs; Lungu, Ovidiu; Stip, Emmanuel; Zaharieva, Vesséla; Lalonde, Pierre; Lipp, Olivier; Mendrek, Adrianna (Frontiers in Psychiatry, 2017)
Background Cigarette smoking is highly prevalent in schizophrenia, and is one of the main factors contributing to the significantly decreased life expectancy in this population. Schizophrenia smokers, compared to their counterparts with no comorbid psychiatric disorder, are largely unaware and indifferent to the long-term negative consequences of cigarette smoking. The objective of this study was to determine, for the first time, if these meta-cognitive deficits are associated with neuro-functional alterations in schizophrenia smokers. Methods Twenty-four smokers with no psychiatric disorder and 21 smokers with schizophrenia (DSM-IV criteria) were scanned using functional magnetic resonance imaging (fMRI) and exposed to anti-smoking images. Granger causality analyses were used to examine the effective connectivity between brain regions found to be significantly activated. Results Across groups, potent activations were observed in the left ventro-lateral prefrontal cortex, the left amygdala and the dorso-medial prefrontal cortex (dmPFC). Using the dmPFC as a seed region, we found an abnormal negative connectivity from the dmPFC to the amygdala in schizophrenia smokers during the viewing of anti-smoking stimuli. This abnormal connectivity was not present during the viewing of aversive stimuli unrelated to tobacco. Discussion Given the well-established roles of the dmPFC in social cognition and of the amygdala in emotional processing, our results suggest that the relative indifference of schizophrenia smokers regarding the negative consequences of tobacco smoking could be explained by a cognitive-affective dissonance.